Austwickiosis in Captive African Spurred Tortoises (Geochelone sulcata) Co-infected with Cryptosporidium ducismarci. (November 2019) - Rostad, Sara J.; Brandão, João; Ramachandran, Akhilesh; Chien, Rory C.; Confer, Anthony W.
Summary: Dermatophilosis has been described in many animals since it was first reported in 1915. In 2010, the genus and species associated with chelonid dermatophilosis was reclassified as Austwickia chelonae. Here we discuss a series of four submissions consisting of eight juvenile African spurred tortoises ( Geochelone sulcata ) from a large breeding facility. Submissions began in December 2016 and continued to June 2017 and then again in November 2018. Clinical signs were originally noted in December of 2015 and consisted of facial swelling and mandibular necrosis that led to complete disarticulation of the mandibles from the skull. Affected animals were emaciated with minimal gastrointestinal contents and several had soft faeces. The facial and head lesions were caused by A. chelonae . Additionally, co-infection with Cryptosporidium ducismarci was discovered within the small intestine. This report gives information on the pathology and pathogenicity of A. chelonae and characterizes the first reported cases of cryptosporidiosis in African spurred tortoises.